ANALISIS TANDA DALAM FILM THE CRUCIFIXION KARYA CHAD HAYES DAN CAREY HAYES SUATU ANALISIS SEMIOTIK - Sumaraw, Eunike Ireine; Rattu, Jultje A.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT This research entitled is Analysis of Signs in The Crucifixion Film: A Semiotic Analysis. The objectives of this research are to identify, classify, and analyze the kinds and meaning of signs in The Crucifixion Film. In this research, the writer uses Pierce’s theory in the process to identifying, classifying and analyzing each scenes and meaning of signs in The Crucifixion Film. The method of this research is descriptive. In doing this research, the writer read some books and journals about signs. The data of signs were collected from every scene which contain sign in the film and analyzed according to Pierce’s theory. The result of this research shows that there are three kinds of signs in film, namely icons, index and symbols. Sign of icons found in 5 scenes namely man and woman, book, sister Adelina and Vaduva, book, and Agares. Sign of indexes found in 9 scenes namely cell iron, blood, costume black, light, insect, strangulation, blood, rain and blood. Sign of symbols are found in 5 scenes namely prayer candles, cross, prohibition, mask and cross. All of this signs contain different meanings. Icons of man and woman mean father Phil’s own, and woman: Nicole’s own. Icons of sister Adelina's and Vaduva’s means Sister Adelina and Vaduva itself. Icons of an exorcism book means a brown book and is a square shaped. Icons of Agares's demonic means a bald-headed demon, and a skull-like body. Icons of an exorcism book means a brown book, is square in shape. Index of the prisoner cell means confinement for the murder of Father Dimitru. Index of the blood means a reaction from within the body of Sister Adelina. Index of the black clothing means shows grief. Index of the flashlight means sing of darkness. Index of the insect means the existence of Agares' resentment towards Nicole. Index of the choking means the resentment of Satan Agares over Sister Vaduva's visit. Index of blood means the fall of Father Gabrielle from the roof of the Church. Index of the rain means mocking uses holy water. Index of blood means a violent impact experienced by Nicole and symbol of the prayer candle means light of Christ, symbol of the cross means life and evidence of strength, symbol of the prohibition means line cannot be passed and the entered, symbol of the mask means a costume for the celebration of the strigoi festival and symbol of the cross means life and evidence of strength. Keywords : Signs, The Crucifixion Film, Semiotic Analysis